Potentiometric and conductimetric studies of chemical equilibria for pyridoxine hydrochloride in aqueous solutions: simple experimental determination of pKa values and analytical applications to pharmaceutical analysis - Santos,Thiago de Almeida Drumond dos (2010)
The combination of two low-cost classical procedures based on titrimetric techniques is presented for the determination of pyridoxine hydrochloride in pharmaceuticals samples. Initially some experiments were carried out aiming to determine both pKa1 and pKa2 values, being those compared to values of literature and theoretical procedures. Commercial samples containing pyridoxine hydrochloride were electrochemically analysed by exploiting their acid-base and precipitation reactions. Potentiometric titrations accomplished the reaction between the ionizable hydrogens present in pyridoxine hydrochloride, being NaOH used as titrant; while the conductimetric method was based on the chemical precipitation between the chloride of pyridoxine hydrochloride molecule and Ag+ ions from de silver nitrate, changing the conductivity of the solution. Both methods were applied to the same commercial samples leading to concordant results when compared by statistical tests (95 and 98% confidence levels). Recoveries ranging from 99.0 to 108.1% were observed, showing no significant interference on the results.